Research trends on the relationship between gut microbiota and colorectal cancer: A bibliometric analysis - Wu, Weigen; Ouyang, Yaobin; Zheng, Pan; Xu, Xinbo; He, Cong; Xie, Chuan; Hong, Junbo; Lu, Nonghua; Zhu, Yin; Li, Nianshuang (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Colorectal cancer (CRC) is the third most common cancer in the world and the second leading cause of cancer-related deaths. Over the past two decades, many researchers have provided a wealth of important information on the role of the gut microbiota in the development and progression of CRC, but a bibliometric study has yet to be conducted to review the current state of research in this area. This study aimed to analyze the current status and future research trends in gut microbiota and CRC through a bibliometric analysis. Methods: Publications from 2001 to 2022 were retrieved from the Web of Science Core Collection database and screened according to inclusion criteria. VOSviewer and CiteSpace software were used to visualize the research trends in this field, including the analysis of title, country, institution, author, number of publications, year of publication, number of citations, journal, and H-index. Results: A total of 863 studies were eventually identified, and the articles retrieved were cited an average of 44.85 times each. The number of publications on this topic has been increased steadily since 2011. China and the USA have made the largest contribution in the field. FRONTIERS IN MICROBIOLOGY is the top productive journal with 26 papers, and Gut journal has the highest average citation (167.23). Shanghai Jiao Tong University is the most contributive institution. Professor Yu J, Sung, Joseph J. Y and Fang JY are the most productive authors in this field. Keyword co-occurrence analysis showed that the terms of “Gut Microbiota”, “Colorectal Cancer”, “Inflammation”, “Probiotic” and “Fusobacterium Nucleatum” were the most frequent, which revealed the research hotpots and trends in this field. Conclusions: There has been a growing number of publications over the past two decades according to the global trends. China and the USA still maintained the leading position in this field. However, collaboration between institutions needs to be strengthened. It’s commended to pay attention to the latest hotspots, such as “F. nucleatum” and “probiotics”. This bibliometric analysis evaluates the scope and trends of gut microbiota and CRC, providing a useful perspective on current research and future directions for studying the field.